2022
DOI: 10.3389/fmicb.2021.784575
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights Into Cadmium Resistance of a Newly Isolated, Plasmid-Free Cellulomonas sp. Strain Y8

Abstract: Our current knowledge on bacterial cadmium (Cd) resistance is mainly based on the functional exploration of specific Cd-resistance genes. In this study, we carried out a genomic study on Cd resistance of a newly isolated Cellulomonas strain with a MIC of 5 mM Cd. Full genome of the strain, with a genome size of 4.47 M bp and GC-content of 75.35%, was obtained through high-quality sequencing. Genome-wide annotations identified 54 heavy metal-related genes. Four potential Cd-resistance genes, namely zntAY8, copA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…The genome contains 2,522 annotated genes (CdSs) with speci c physiological functions, accounting for 88.27% of the entire genome, as annotated in various databases (Table S2). The circular genome map of Enterococcus faecalis strain ATCC19433 provides an overview of key genomic features, including the distribution of genes on both the positive and antisense strands, COG functional annotation of genes, G + C content, homologous genes, and les for rRNA and tRNA, which could support research on the mechanism of Cd resistance and binding [50].…”
Section: Genome Propertiesmentioning
confidence: 99%
“…The genome contains 2,522 annotated genes (CdSs) with speci c physiological functions, accounting for 88.27% of the entire genome, as annotated in various databases (Table S2). The circular genome map of Enterococcus faecalis strain ATCC19433 provides an overview of key genomic features, including the distribution of genes on both the positive and antisense strands, COG functional annotation of genes, G + C content, homologous genes, and les for rRNA and tRNA, which could support research on the mechanism of Cd resistance and binding [50].…”
Section: Genome Propertiesmentioning
confidence: 99%
“…Firstly, the speci c mechanisms of cadmium resistance in bacteria are not understood comprehensibly. While certain genes associated with cadmium resistance, such as czcC, czcB, czcA, czcR, czcS, cadA and cadR, have been identi ed, there might be many other genes involved (Abbas et al 2018;Qin et al 2019;Chen et al 2022). Secondly, the role of time and dosage related to cadmium resistance is still questionable.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O. The cellular response in making the defence system ready for cadmium assaults is modulated differentially when grown in lower concentrations of Cd 2+ , indicating that lower cadmium concentrations can activate e ux mechanisms more effectively in lesser preparatory time(Chen et al 2022), especially when shifted to a fresh medium with abruptly high cadmium (1.5 mM).This study has also described the effect of zinc or cobalt concentrations in the pre-culture (i.e., zinc or cobaltinduced cells) on cadmium resistance in CD3. It was shown that the cells' resistance to cadmium was in uenced by pre-growing them in the presence of ZnSO 4 .7H 2 O (0.25 mM).…”
mentioning
confidence: 99%